Kombinasi Terapi Nebulizer dan Fisioterapi Dada terhadap Bersihan Jalan Napas pada Anak Bronkopneumonia: Studi Kasus - Desi Mirnasari; Dwiyanti Purbasari; Nonok Kalina (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Background: Pneumonia is one of the leading causes of morbidity among children in Indonesia. In 2023, Central Java Province was estimated to have 134,708 cases of pneumonia among children under five, indicating that pneumonia remains a significant child health problem. Children with bronchopneumonia often experience mucus accumulation in the airways, resulting in impaired airway clearance and disrupted ventilation. Objective: To identify the effectiveness of a combination of nebulizer therapy and chest physiotherapy in improving airway clearance among children with bronchopneumonia. Methods: This study employed a qualitative method with a case study design involving two pediatric patients diagnosed with bronchopneumonia and the nursing diagnosis of ineffective airway clearance. The study was conducted from December 15–17 and December 22–24, 2025, in the pediatric ward of Kardinah Regional General Hospital, Tegal City. Data were collected through anamnesis, observation, physical examination, documentation review, and analysis of supporting diagnostic examinations. The intervention consisted of a combination of nebulizer therapy and chest physiotherapy administered for three consecutive days to each patient. Results: Evaluation on the third day showed improvement in the respiratory condition of both patients. The patients appeared more comfortable, experienced reduced dyspnea and coughing frequency, and were able to expectorate secretions more effectively. In addition, improvements were observed in airway clearance outcome indicators, including reduced adventitious breath sounds, improved breathing patterns, decreased sputum retention, and enhanced airway patency. Conclusion: The combination of nebulizer therapy and chest physiotherapy administered regularly for three days was effective in improving airway clearance in children with bronchopneumonia and can be used as a nursing intervention in the management of airway clearance problems